Why Broadband? The Meaning of Broadband for Residential Users - Van den Broeck, Wendy; Lievens, Bram (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2007)
In the society we live in today, access to information is crucial. But because of the increased amount of data as well as the nature of the content, a simple Internet connection is no longer sufficient. The EU government, which has followed an Internet access policy for many years (see eEurope programme), has shifted the focus to broadband Internet. Yet, despite these efforts, the uptake of broadband Internet is still quite low. And the situation in developing countries is even more critical. But is access to information the only enabler for users to switch to a broadband connection? With the wide range of Internet services and applications in the domains of entertainment, communication, commerce etc, now more than ever the Internet is a part of people’s everyday life. In this article we will not only look at the benefits and motivations for people to subscribe to a broadband Internet connection, but also at the different barriers to the uptake and usage of such a connection.